PERAN PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN PADA KANTOR KELURAHAN DADI MULYA KOTA SAMARINDA - Ratnasari, Desi (PREDIKSI, 2016)
The purpose of this research is to knowing how community participation in development planning , especially in Sub Dadi Mulya District of Samarinda Ulu . The method used in this study is a research method by using a qualitative approach , where research is descriptive . Analysis technique used in this research is qualitative descriptive analysis . Based on these results and in accordance with the answers given on the informant told investigators that community participation in the provision of proposed or in development planning is very important but community participation in development planning in the village of Dadi Mulya not maximized because most people lack the knowledge to become a factor resistor in village development planning , and coming to his development plans are just some people who have a deeper understanding .